Prevention of Emotional Disorders and Symptoms Under Health Conditions: A Pilot Study using the Unified Protocol in a Fertility Unit - Martínez-Borba, Verónica; Osma, Jorge; Crespo-Delgado, Elena; Andreu-Pejo, Laura; Monferrer-Serrano, Alba (Anales de Psicología / Annals of Psychology, 2022)
Emotional Disorders (EDs) are common in women who undergo fertility treatments. The Unified Protocol (UP) is a transdiagnostic intervention that has demonstrated efficacy in preventing EDs under different health conditions. The aim of this pilot study is to: 1) improve emotional dysregulation for the prevention of anxiety and depressive symptoms in women undergoing intrauterine inseminations (IUI); 2) assess their acceptability (e.g., satisfaction and adherence rates). Method: Five women undergoing IUI, with no clinical diagnoses, responded to measures of mood (anxiety and depression), affect, quality of life and emotional dysregulation in the pre- and post-assessments, and at the 1-, 3- and 6-month follow-ups. The UP was adapted to be applied during six face-to-face group sessions lasting 2 h. The COVID-19 pandemic situation implied changing to an online format to end the program. Results: The results showed that women did not develop EDs, and no statistically significant pre-post and pre-follow-up differences were found for anxiety, depression, quality of life and emotional dysregulation (all p > .050). A tendency towards improvement in the post-assessment evaluation was noted. Satisfaction with the format and UP program was high. Conclusions: It would seem that programs focusing on therapeutic common factors like the UP could have an emotional preventive effect during IUI.